Lotsizing and scheduling by batch sequencing - Carsten Jordan; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
The discrete lotsizing and scheduling problem with setup-times is transformed into a single-machine scheduling problem, denoted as batch sequencing problem, which integrates sequence-dependent setups as well. The relationship between the lotsizing and the batch sequencing problem is analyzed. The batch sequencing problem is solved with an enumerative algorithm which is accelerated through bounding and dominance rules. Computational results show that this algorithm solves even the special case of sequence-independent setups more efficiently than a procedure for the discrete lotsizing and scheduling problem which has been recently published.
Keywords: 650; Discrete Lotsizing And Scheduling; Setup-Times; Batch Sequencing; Sequencing Algorithm; Bounding/ Dominance Rules; Produktionssteuerung; Theorie